2019
DOI: 10.5194/nhess-19-2405-2019
|View full text |Cite
|
Sign up to set email alerts
|

An integrated evaluation of the National Water Model (NWM)–Height Above Nearest Drainage (HAND) flood mapping methodology

Abstract: Abstract. Flood maps are needed for emergency response, research, and planning. The Height Above Nearest Drainage (HAND) technique is a low-complexity, terrain-based approach for inundation mapping using elevation data, discharge–height relationships, and streamflow inputs. The recent operational capacities of the NOAA National Water Model (NWM) and preprocessed HAND products from the University of Texas offer an operational framework for real-time and forecast flood guidance across the US. In this study, we e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 19 publications
1
77
0
Order By: Relevance
“…Our mapping approach, while simple in its representation of process, produces floodplain maps with a high rate of agreement to those created with a hydraulic model, which has a more robust representation of process, but is data intensive and has greater computational demands. As such, our work supports the assessment that a new generation of floodplain mapping approaches, notably those classified as low-complexity, has great promise to improve upon our understanding and communication of flood risk and conservation practices [18,20,24,48].…”
Section: Utility Of the Probhand Model For Communicating Flood Hazardssupporting
confidence: 63%
See 2 more Smart Citations
“…Our mapping approach, while simple in its representation of process, produces floodplain maps with a high rate of agreement to those created with a hydraulic model, which has a more robust representation of process, but is data intensive and has greater computational demands. As such, our work supports the assessment that a new generation of floodplain mapping approaches, notably those classified as low-complexity, has great promise to improve upon our understanding and communication of flood risk and conservation practices [18,20,24,48].…”
Section: Utility Of the Probhand Model For Communicating Flood Hazardssupporting
confidence: 63%
“…In its current form, the probHAND product is unlikely suitable to support the NFIP and the determination of flood insurance rates. Although the probHAND had better agreement with the calibrated hydraulic model, than did the DFIRM, documented local uncertainties, both in our model and elsewhere, are likely too high to identify the flood risk for a single property [ 24 , 50 ]. It may, however, provide a good resource for other flood risk management applications, including public education and emergency planning, notably over regional scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible source of uncertainty is the absence of connection between floodplains associated with each river reach: water cannot flow into pixels which are not connected to the considered river section, which may be particularly problematic at confluences of flat and wide floodplains. Johnson et al (2019) conclude that significant errors may be observed for both low-order upstream river reaches, and downstream and flat floodplains.…”
Section: Introductionmentioning
confidence: 83%
“…These methods are applied either directly from the DTM for the AutoRoute method (Follum et al, 2017(Follum et al, , 2020, or from a Height Above Nearest Drainage raster (Nobre et al, 2011) derived from the DTM: f2HAND (Speckhann et al, 2017); Geoflood ; MHYST (Rebolho et al, 2018); Hydrogeomorphic FHM (Tavares da Costa et al, 2019). All these methods determine a local discharge/height relationship from i) the cross-section and longitudinal profile geometries extracted from the DTM (locally for Autoroute, averaged at river reach scale for HAND-based approaches), and ii) a local hydraulic formula: Manning-Strickler (Zheng Xing et al, 2018;Johnson et al, 2019;Garousi-Nejad et al, 2019) or Debord (Rebolho et al, 2018). These approaches are very efficient in terms of computation times, and can therefore be suitable for real time inundation forecasting at continental scales (Liu Yan Y. et al, 2018), or for probabilistic or multi-scenario modelling (Teng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%